How to address heuristics and cognitive biases in tax decision-making: A systematic literature review - Setiyani, Ria; Septiani, Tika (Publisher of Widyagama University of Malang (UWG Press), 2024)
Heuristic and cognitive biases in Indonesia have caused tax compliance issues, as public prejudice leads to tax avoidance, and overconfidence among authorities results in less effective tax policies. This study aims to investigate the use of heuristics and cognitive biases in tax decision-making by individuals and businesses. It examined tax decision-making using heuristics and cognitive biases in tax decision-making, selecting 25 recent research articles from scientific journals. The research shows that using heuristics can lead to biases and errors among individual taxpayers and professionals. To mitigate this issue, adopting a comprehensive approach that includes educational initiatives, integration of advanced technology, establishment of structured decision-making processes, promotion of interdisciplinary collaboration, and fostering a culture of critical analysis within tax-related organizations is important. Therefore, addressing biases driven by heuristics in tax decision-making requires a combination of educational efforts, technological advancements, and cooperative and interdisciplinary efforts to enhance the accuracy and efficiency of decision-making.JEL ClassificationÂ D91; G40; M41